Culturally Responsive Teaching Approach in Differentiated Learning on Students’ Learning Interests and Learning Outcomes - Harmilawati, Harmilawati; Aminah, Siti; Sabaruddin, Sabaruddin; Khaerati Syam, Ummi; Khaerunnisa, Khaerunnisa; Mujahid, Ayinun (Universitas Islam Ahmad Dahlan (UIAD), 2024)
The implementation of the independent curriculum continues to raise numerous questions among educators. Teachers face the challenge of adapting to and successfully implementing this curriculum by employing engaging media and effective learning strategies tailored to their respective disciplines. This is especially crucial in the context of English language instruction, a subject often perceived as difficult by students. One potential solution to address these challenges is the adoption of differentiated learning strategies. Differentiated learning aims to unlock and maximize the potential of every student by aligning instructional methods with their individual needs, readiness levels, interests, and learning profiles. Within this framework, Cultural Responsive Teaching (CRT) emerges as a valuable approach, enabling educators to create inclusive and culturally relevant learning experiences that resonate with diverse student backgrounds. This study investigates the implementation of CRT in supporting differentiated learning strategies in English language education. Utilizing a pre-experimental design, the research was conducted at MAS Darul Qalam Bulukumba. Data collection methods included administering questionnaires to assess student interest and conducting pre- and post-tests to measure learning outcomes. The findings reveal a significant positive improvement in students' interest in learning English after the introduction of CRT, compared to their interest levels prior to its implementation. Additionally, the analysis of test results indicates a notable increase in students' academic performance, demonstrating the effectiveness of CRT in fostering both engagement and achievement. These results highlight the potential of CRT as a transformative tool in enhancing English language learning in the context of the independent curriculum.